Higher prevalence of childbirth related fear in foreign born pregnant women – Findings from a community sample in Sweden. Issue 4 (April 2015) - Ternström, Elin; Hildingsson, Ingegerd; Haines, Helen; Rubertsson, Christine
Abstract: Objective: to investigate the prevalence of childbirth related fear (CBRF) in early pregnancy among both Swedish born and foreign born women living in Sweden. Design: a cross sectional prevalence study. Data was collected by a questionnaire, which was available in Swedish and eight other languages. Setting: a university hospital in the middle of Sweden. Participants: the recruitment took place during a two month period where the participating women completed the Fear of Birth Scale (FOBS) in mid-pregnancy. Measurements: prevalence of CBRF, the cut-point of 60 and above. Odds ratios with a 95% confidence interval were calculated between women born in Sweden and women born in a foreign country. Stratified analyses were also performed separately for Swedish born and foreign born women. Findings: in total 606 women completed the survey, 78% were born in Sweden and 22% were born in a foreign country. About 22% of the total sample scored 60 or more on the FOBS-scale. Almost 18% ( n =85) of the women born in Sweden reported CBRF whereas 37 % ( n =49) of the foreign born women reported CBRF. Being born outside Sweden (OR 2.7; CI 1.7–4.0) and expecting the first baby (OR 1.9; CI 1.3–2.8) were associated with CBRF. There were no differences in age, civil status or level of education between women with or without FOBS≥60. However, a stratified analysis showed that primiparas born in a foreign country (OR 3.8; CI 1.8–8.0) were more likely to score 60 or more on the FOBS-scale compared to multiparas born in a foreign country. Key conclusions: childbirth related fear was almost three times as common among foreign born women when compared to Swedish women. Foreign born childbearing women are an extremely vulnerable group who need culturally sensitive and targeted support from caregivers. Further research is needed to clearly identify the components of women׳s childbirth related fear in various ethnic groups.